2022
DOI: 10.1007/s12571-022-01331-7
|View full text |Cite
|
Sign up to set email alerts
|

Stories of change in nutrition in Burkina Faso 1992–2018: a macro-level perspective

Abstract: Looking back at the development of successful enabling environments for nutrition may inform policymakers on how to accelerate progress to end all forms of malnutrition by 2030. As under-five stunting declined substantially in Burkina Faso, from a peak at 45% in 1998/99 to 25% in 2018, we analyzed through a stories of change approach the actors, ideas, initiatives, policies and capacities which enabled wide-scale nutrition progress. We triangulated findings from policy analysis, stakeholder mapping, and nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…For the same region, [18] studied the relationship of flood recessions and food security related to water management activities. Another host of recent studies revealed that food insecurity mostly occurred in rural areas due to inappropriate infrastructure and food storage systems, as well as donor tensions or reduced incomes [19,20]. From a different view, [21] investigated the link between climate change and farming activities with an emphasis on the perception of local farmers to support the agricultural and nutritional requirements in Burkina Faso.…”
Section: Introductionmentioning
confidence: 99%
“…For the same region, [18] studied the relationship of flood recessions and food security related to water management activities. Another host of recent studies revealed that food insecurity mostly occurred in rural areas due to inappropriate infrastructure and food storage systems, as well as donor tensions or reduced incomes [19,20]. From a different view, [21] investigated the link between climate change and farming activities with an emphasis on the perception of local farmers to support the agricultural and nutritional requirements in Burkina Faso.…”
Section: Introductionmentioning
confidence: 99%
“…We focus our analysis on Burkina Faso because it is an example of a low-income country that has long been facing development challenges from existing stressors including climate change (Brown & Crawford, 2008), in part manifested in increasing temperatures, a downward trend in overall rainfall but an increase in heavy precipitation days. Despite food security worsening across the Sahel region, Burkina Faso has improved its human development indicators, including reducing child mortality, in part through investing in women's access to universal health care (Samb & Ridde, 2018), and a focus on improved nutrition (Turowska et al, 2022). Yet, climate change may well negate these improvements.…”
Section: Introductionmentioning
confidence: 99%
“…The Direction of Nutrition was created in the Ministry of Health in 2002 and it has taken leadership on the nutritional agenda since then. It advocated and prioritized the nutritional agenda and coordinated intersectoral collaboration, which contributed to nutritional improvement in Burkina Faso; however, there has been difficulty in ensuring funding and human resources at the decentralized level [ 6 ]. In addition, political instability, emerging conflicts and displacement, climate change, and rapid population growth have been challenges for food security and nutrition in Burkina Faso.…”
Section: Introductionmentioning
confidence: 99%